Impact of Digital Media Marketing on Purchase Intention of Organic Vegetables in Butwal Sub-Metropolitan City, Nepal - Shrestha, Subham (KMC Journal, 2026)
This study investigates how digital media marketing influences consumers purchase intention toward organic vegetables in Butwal Sub-Metropolitan City, Nepal. By using four constructs of environmental concern, price, availability, and trust, this study uses a quantitative research design and surveys 403 respondents familiar with digital media platforms by using a questionnaire. Using partial least squares structural equation modeling (PLS-SEM), the analysis evaluates the reliability and validity of the reflective measurement model and then examines the structural relationships among the latent variables to identify the key determinants of purchase intention. The findings show that environmental concern, price, and trust are positive and significant determinants of purchase intention, whereas availability has a positive but insignificant effect. The model demonstrates moderate predictive capability (R² = 0.458), and the Importance–Performance Map Analysis indicates that environmental concern is the strongest driver of purchase intention for organic vegetables in Butwal. Overall, the study concludes that digital media marketing can strongly enhance purchase intention when a marketer emphasizes environmental benefits, transparency, and value-based pricing. These insights can help farmers, producers, resellers, and marketers design and align with digital media strategies to promote and increase purchase intention for organic vegetables in developing markets.